Pelatihan Baca Tulis Arab Pegon Bagi Santri Madrasah Diniyah di Pesantren Bustanu Usyaqil Qur’an Kaliwungu Ngunut Tulungagung - Tika, Tika Mardiyah; Fudhaili, Achmad; Amrullah, Ahmad Fikri; Mardiyana, Alfa; Nuha, Muhammad Afthon Ulin (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2023)
Pegon arabic reading writing and the kitab kuning are two things that must go hand in hand. Mastery of absolute pegon arabic reading and writing is necessary for learning the kitab kuning. The purpose of the pegon arabic reading and writing training at the Bustanu Usyaqil Qur'an Islamic boarding school is to provide students with mastery and skills in studying the kitab kuning who will graduate from the Ula level (dirasah qur'aniyah). This activity uses a participatory action research (PAR) approach through training methods and learning assistance with the stages: initial mapping, building relationships with the community, participatory mapping, developing movement strategies, implementing change actions, evaluating and reflecting. From the training that has been given, the students master the pegon arabic writing pattern and they can apply it in giving the meaning of the kitab as well as being able to read it correctly. Thus the pegon arabic reading and writing training at the Bustanu Usyaqil Qur'an Islamic boarding school is a provision for students at the Ula level (dirasah qur'aniyah) to master the Javanese pegon arabic reading and writing skills so that they are ready to take part in the study of the kitab kuning.